Solution-phase combinatorial synthesis of isoxazolines and isoxazoles using [2+3] cycloaddition reaction of nitrile oxides - Kang, KH; Pae, AN; Choi, KI; Cho, YS; Chung, BY; Lee, JE; Jung, SH; Koh, HY; Lee, HY (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
An efficient way to construct a library of isoxazoles and isoxazolines was developed by solution-phase 1,3-dipolar cycloaddition reaction of nitrile oxides with olefins and alkynes followed by precipitation of the products as HCl salts. (C) 2001 Elsevier Science Ltd. All rights reserved.